2009
DOI: 10.1098/rsbl.2009.0474
|View full text |Cite
|
Sign up to set email alerts
|

Predictive motor activation during action observation in human infants

Abstract: Certain regions of the human brain are activated both during action execution and action observation. This so-called 'mirror neuron system' has been proposed to enable an observer to understand an action through a process of internal motor simulation. Although there has been much speculation about the existence of such a system from early in life, to date there is little direct evidence that young infants recruit brain areas involved in action production during action observation. To address this question, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
255
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(275 citation statements)
references
References 18 publications
18
255
1
1
Order By: Relevance
“…Several prior studies (Southgate et al, 2009;Marshall et al, 2011;Saby et al, 2013) also reported mu-suppression in toddlers during action observation. The current study goes further not only by employing a socially interactive paradigm and by precisely quantifying and controlling for toddlers' motor activity, but also by (1) locking toddlers' EEG to the onset and offset of their own or their mother's actions; (2) identifying mu suppression using multiple criteria including ERSP, PSD, scalp maps and source locations; and (3) comparing EEG power profiles across a wide range of frequencies and channel locations.…”
Section: Mu Desynchronization In Childrenmentioning
confidence: 98%
“…Several prior studies (Southgate et al, 2009;Marshall et al, 2011;Saby et al, 2013) also reported mu-suppression in toddlers during action observation. The current study goes further not only by employing a socially interactive paradigm and by precisely quantifying and controlling for toddlers' motor activity, but also by (1) locking toddlers' EEG to the onset and offset of their own or their mother's actions; (2) identifying mu suppression using multiple criteria including ERSP, PSD, scalp maps and source locations; and (3) comparing EEG power profiles across a wide range of frequencies and channel locations.…”
Section: Mu Desynchronization In Childrenmentioning
confidence: 98%
“…Previous infant studies investigated neural mirroring during the observation of live (e.g., Nyström et al, 2010;Southgate et al, 2009) or video actions (e.g., Nyström, 2008van Elk et al, 2008). The majority of the researchers used live stimuli reasoning that live stimuli provide a more realistic view on brain processing because these stimuli are efficiently processed due to their similarity with the real world (Carver et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Neuro physiological [1][2][3][4][5][6][7] and brainimaging [8][9][10][11] studies indicate that others' actions are understood through a direct match ing process of a mirror neuron system (MNS), where an observed action is mapped onto the observer's own motor representation of that action 12,13 . In fact, several recent neurophysiological studies with infants over the age of 6 months have shown MNS function ing when the infants observed others' actions [14][15][16][17][18][19] . In spite of this correlation, compelling evidence of the direct matching process in early infancy is rare.…”
mentioning
confidence: 99%
“…Recent neurophysiological studies found that motor activation in areas associated with the MNS occurred immediately prior to the onset of observed actions in adults 20 and 9montholds 17 . Moreover, recent behavioural studies showed that adults 21 and 12monthold infants 22 manifest proactive goaldirected eye movements while observing the manipulating actions of others.…”
mentioning
confidence: 99%
See 1 more Smart Citation